The Platonic Receptacle (Hypodoché), Whitehead's Philosophy, and Genome Evolution - Svoboda, Jan; Svoboda, Jan (Viruses, 2017)
The discovery of a universal genetic code utilized by all existing organisms became the backbone of biology. The coding capacity underwent changes during evolution, but its main fluctuation results from its different reading and regulation. The genetic code thus represents a sort of receptacle of living organism evolution. In this article, we propose an analogy between the genetic code and a broader Platonic hypodoché, a concept that Alfred North Whitehead used to explain various aspects of science.
Keywords: evolution changes; Genetic Code; Platonic receptacle; Models, Biological; Whitehead’s argument; genetický kód; biologické modely; realization of ideas; present day genetics; genetic code; molekulární evoluce; Evolution, Molecular